REGULATORY ROLE OF ETV4 IN EMBRYONIC STEM CELL FATE: INSIGHTS INTO MECHANOTRANSDUCTION AND LINEAGE DETERMINATION - Ardiana, Asa (Journal of Stem Cell Research and Tissue Engineering, 2024)
Conventional cell biology studies focus on cellular responses to chemical signals, but cells also react to mechanical cues like density, size, and substrate rigidity, activating specific gene expression. Embryo development leads to the formation of a gastrula, establishing body structure and germ layers (endoderm, ectoderm, mesoderm) via diverse mechanisms. In humans, gastrulation begins with the Primitive Streak (PS) and T gene expression, guiding epiblast cell migration. Self-regulation occurs in gastruloid models, derived from human embryonic stem cells, capable of differentiation. Mediators like YAP/TAZ and PIEZO1 link density to cellular responses, with ETV4 serving as a link between mechanical environment and gene expression. This research employed a systematic literature review to synthesize relevant studies. Inspired by stem cell advancements, particularly ETV4's role, searches on PubMed yielded three articles meeting inclusion criteria. ES cells maintain undifferentiated states via ETV4 and ETV5. Rapid cell growth deactivates ETV4, prompting differentiation, influenced by mechanical cues. ETV4, ETV5, and SPRY4 regulate the FGF/ERK pathway, modulating sensitivity. High density initiates neuroectodermal cell formation, impacting integrin-actomyosin and FGFR pathways, via ETV4. Fluctuations in density dictate lineage fate, with ETV4 as a key sensor, linking density shifts to lineage determination via the ERK pathway.